Identifikasi Salt and Pepper Noise pada Citra dengan Metode Median Filter - Steven Gerald Parsaoran Berutu,; I Komang Ari Mogi, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Noise is a common issue in image processing that can degrade the quality and clarity of images. In this research, we propose a method for identifying the levels of salt and pepper noise in images using the median filter technique. The median filter is a non-linear filtering approach that effectively reduces noise by replacing the pixel values with the median value of neighboring pixels. In our approach, we apply the median filter to the image and observe the changes in the pixel values. By analyzing the differences between the original image and the filtered image, we can determine the extent of salt and pepper noise present in the image. The proposed method offers a reliable and efficient way to quantify the level of salt and pepper noise. Experimental results on various images demonstrate the effectiveness of the proposed method in accurately identifying and quantifying salt and pepper noise levels. The method provides valuable insights into the amount of noise present in images, enabling better understanding and further processing of the image data.